The time-varying effects of economic policy uncertainty and low-carbon economic transition on enterprise innovation in China - Zhang, Lin; Shao, Chonglin; Wang, Jia (Frontiers in Environmental Science, 2023)
In the study, a three-variable time-varying vector autoregressive (TVP-VAR) model with stochastic volatility was used to investigate the nonlinear dynamic effects of economic policy uncertainty and low-carbon economic transition on enterprise innovation in China. The sample data cover the period between Q1 1995 and Q4 2021.It is found that the influence of economic policy uncertainty on enterprise innovation is time-varying and asymmetrical, especially with the 2008 financial crisis as the turning point. After the financial crisis, the positive impact of economic policy uncertainty on enterprises has been weakening, and in 2015, the positive impact turned into a negative impact. In general, economic policy uncertainty is not conducive to the transition to low-carbon economic transition, and with the outbreak of the financial crisis in 2008, the negative impact reached a negative peak. The low-carbon economic transition has a significant crowding-out effect on enterprise innovation, while enterprise innovation has a significant spillover effect on low-carbon economic transition. The conclusion can provide the scientific basis for enterprises to adapt to the change in the economic environment to complete low-carbon economic transition and formulate innovation strategies, which is conducive to the sustainable development of the ecological environment and economic society.